COMPARISION OF RESPONSE OF GROUNDNUT GENOTYPES AT DIFFERENT PHOSPHORUS LEVELS - AJAY B.C*, SINGH A.L., BERA S.K., NARENDRA KUMAR, DAGLA M.C; K.C. NATARAJ (The Journal of Research ANGRAU, 2019)
Low phosphorus (P) availability in soil is one of the limiting factors affecting groundnut productivity by reducing leaf area and dry weight. This study evaluated groundnut genotypes for their ability to thrive and produce on calcareous soils with low phosphorus availability. Assessment of shoot biomass, root biomass, shoot Pconcentration, kernel P-concentration, P-accumulation and yield were completed using three phosphorus levels and 23 groundnut genotypes. Study was conducted with three phosphorus levels namely no (P0), normal P (P50) and high P (P100) as the main factor with genotypes as second factor arranged in a factorial completely randomized design. Significant genotypic differences were observed for the characters studied. Shoot P-concentration and accumulation increased with increase in phosphorus levels, whereas, root biomass and kernel P-concentration decreased with increase in phosphorus levels. There was varying response of genotypes for yield, kernel Pconcentration and accumulation, shoot P-concentration and accumulation, biomass and harvest index. In addition, genotypes ICG-221, GG-5, TG-37A and FeESG-10 were designated as ‘high yielder–non-responsive’, whereas, genotypes NRCG-15049, TPG-41, GPBD-4 and NRCG-3498 were identified as ‘low yielder - responsive’. These genotypes can be used in breeding programs to develop ‘high-yielder– responsive’ genotypes.